Analysis of Factors and Development Potential of Economic Clusters by Economic Activities in Mari El Republic - Golovin, Viktor Aleksandrovich (Economy of Regions, 2017)
This article analyzes the factors that drive the development of economic clusters in Mari El Republic (Russia). This analysis allowed to reveal the potential of those clusters further development. I consider a shift-share method as one of the major methods to identify the factors that determine the expansion of economic clusters. The author proposes the modification of shift-share method using relative performance indicators to evaluate the intensity and quality of clustering processes in the region. The article presents the results of empirical research of the economy of Mari El Republic by shift-share method (2005-2015 years) in the context of economic activities according to the Federal State Statistics Service. After the analysis of three basic indicators, the leading and lagging economic activities were revealed for the period of 10 years. I paid special attention to the analysis of clustering potential of the Mari El Republic in the context of economic activities based on the Clustering Potential Index. This analysis shows promising economic activities and industries that may form cluster. The author discusses the compliance and possible conflicts of two methods used in the study. Further research of this field can focus on the of system analysis and identifying specific companies and production chains that form the basis of clustering.